Android OS vulnerabilities :analysis and categorization (2017)
Android devices are increasingly used in everyday life. They incorporate most of our private data. This data becomes the target of attacks that exploit Android vulnerabilities. To this day, a study has not been carried out on all the vulnerabilities that affect the Android operating system. In addition, there is no official taxonomy to catalog vulnerabilities, and there is no way to detect it at the time of development. The objective of this study is to (i) define the taxonomy of the types of vulnerabilities related to Android; (ii) investigate the layers and subsystems impacted by Android; (iii) study the survival of vulnerabilities; (iv) analyze the evolution of these vulnerabilities; and (v) determine the correlation between vulnerability types and CVSS vectors. These findings would be the starting point to improve the development process for Android and define a way to detect vulnerabilities during development